Alcohol, pattern of drinking and all‐cause mortality in Russia, Belarus and Hungary: a retrospective indirect cohort study based on mortality of relatives. (23rd March 2018) - Horvat, Pia; Stefler, Denes; Murphy, Michael; King, Lawrence; McKee, Martin; Bobak, Martin
Abstract: Aims: To assess the relationship between alcohol intake frequency and mortality among males and females in three Eastern European populations, and to estimate the additional mortality risk posed by a combination of frequent drinking, binge drinking and other hazardous drinking habits. Design: Retrospective cohort study; the cohort consisted of close relatives of survey participants. Setting: Middle‐sized settlements in Russia, Belarus and Hungary. Participants: A total of 124 150 subjects aged 35–69 years in 1998 and followed‐up until 2013. Measurements: Survey respondents provided information on their mothers, fathers, siblings and partners of female respondents. This information, including current vital status and dates of birth and death, was used to construct the cohort of relatives. Alcohol consumption indices, reported by survey participants, included drinking frequency, binge drinking and hazardous drinking [consuming non‐beverage and/or illicitly‐produced alcohol and/or heavy drinking over several days ( zapoi in Russian)]. Findings: Drinking frequency was associated positively with mortality in all three countries and both genders. At each drinking frequency level, mortality risk increased among those who also engaged in binge and/or hazardous drinking. Regular male drinkers who were also binge drinkers and hazardous drinkers had the highest risk of death; their hazard ratios (HR), compared with non‐binge‐non‐hazardous occasional drinkers, were 2.56 [95% confidence interval (CI) = 2.27–2.88], 2.14 (95% CI = 1.84–2.48) and 2.11 (95% CI = 1.90–2.35) in Russia, Belarus and Hungary, respectively. In women, the corresponding HRs (using a lower frequency cut‐off) were 2.86 (95% CI = 1.99–4.12) in Russia, 3.44 (95% CI = 2.17–5.44) in Belarus and 3.01 (95% CI = 2.26–4.01) in Hungary. Conclusions: Drinking frequency is associated positively with mortality among men and women in Russia, Belarus and Hungary. The mortality risk is higher among frequent drinkers who exhibit binge and hazardous drinking patterns.